Increased expression of the TLR7/9 signaling pathways in chronic active EBV infection - Liu, Luyao; Wang, Ying; Wang, Wenjie; Ying, Wenjing; Sun, Bijun; Wang, Xiaochuan; Sun, Jinqiao (Frontiers in Pediatrics, 2022)
We aimed to investigate the immunological mechanisms of the Toll-like receptor (TLR) signaling pathways in different types of Epstein-Barr virus (EBV) infection. We retrospectively summarized the clinical data, routine laboratory tests and the immunological function of the infectious mononucleosis (IM) and chronic active EBV infection (CAEBV) patients. A real-time quantitative PCR array was used to detect the mRNA expression levels of TLR7/TLR9 and myeloid-differentiation factor 88 (MyD88). Flow cytometry was used to detect the protein expression of TLR7/TLR9. The MyD88 and nuclear factor-κB (NF-κB) (p65) protein were detected by western blotting. A cytometric bead array (CBA) assay was used to detect the expression of downstream cytokines. CAEBV patients presented with increased expression of TLR7/TLR9 in monocytes and B lymphocytes. TLR9 expression in the B lymphocytes of IM patients was decreased compared with the CAEBV pateints. Downstream signaling mediators, including MyD88 and NF-κB, were revealed to be increased in EBV-infected patients. Moreover, the expression of MyD88 and NF-κB was higher in CAEBV patients, leading to disrupted balance of downstream cytokines. EBV may activate the immune system via TLR7/TLR9 signaling pathways. Moreover, the overactivated TLR7/TLR9 pathway in CAEBV patients resulted in excessive inflammation, which might be relevant to the poor prognosis.